Managing with power : politics and influence in organizations - Pfeffer, Jeffrey (Boston, Mass. : Harvard Business School Press, 1992)
Although much has been written about how to make better decisions, a decision by itself changes nothing. The big problem facing managers and their organizations today is one of implementation--how to get things done in a timely and effective way. Stanford Business School Professor Jeffrey Pfeffer argues that problems of implementation are really issues of how to influence behavior, change the course of events, overcome resistance, and get people to do things they would.
not otherwise do. In a word, power. Managing with Power provides an in-depth look at the role of power and influence in organizations. Power is often disparaged, yet Pfeffer shows convincingly that its effective use is an essential component of strong leadership. With vivid examples from Lyndon Johnson and Henry Kissinger to John Sculley and Henry Ford, he makes a compelling case for the necessity of power in mobilizing the political support and resources to get things.
done in any organization. And he provides a fascinating look at the personal attributes--such as flexibility, stamina, and a high tolerance for conflict--and the structural factors--such as control of resources, access to information, and formal authority--that can help managers advance organizational goals and achieve individual success. Pfeffer begins his comprehensive evaluation of power by helping managers recognize situations that involve the use of power, and shows.
how to identify the principal actors and their likely points of view. He then looks at the different sources of power, and explains why some organizations and people use power more effectively than others. Next, he explores the specific strategies and tactics through which power and influence are used--how they help managers achieve tangible results. And finally, he considers issues of power dynamics: how power is lost, the role of power in the process of organizational.
change, and the positive and negative consequences of power for organizations. Politics and influence, the mechanisms by which power is realized, are unavoidable components of any business--indeed, any organization. Pfeffer shows that by understanding where power comes from and how it can be used effectively, managers can help their organizations, and themselves, "achieve great things."
Decisions and implementation -- When is power used? -- Diagnosing power and dependence -- Where does power come from? -- Resources, allies, and the new golden rule -- Location in the communication network -- Formal authority, reputation, and performance -- The importance of being in the right unit -- Individual attributes as sources of power -- Framing : how we look at things affects how they look -- Interpersonal influence -- Timing is (almost) everything -- The politics of information and analysis -- Changing the structure to consolidate power -- Symbolic action : language, ceremonies, and settings -- Even the mighty fall : how power is lost -- Managing political dynamics productively -- Managing with power.
Includes bibliographical references (pages 367-377) and index.
Description based on print version record.
Keywords: Decision making; Power (Social sciences); Organizational behavior; Management; Macht; Besluitvorming; Prise de décision; Pouvoir (Sciences sociales); Comportement organisationnel; Decision making; Organizational behavior; Power (Social sciences); BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books